2012
DOI: 10.1007/s10453-012-9270-2
|View full text |Cite
|
Sign up to set email alerts
|

Transport of airborne Picea schrenkiana pollen on the northern slope of Tianshan Mountains (Xinjiang, China) and its implication for paleoenvironmental reconstruction

Abstract: The understanding of airborne pollen transportation is crucial for the reconstruction of the paleoenvironment. Under favorable conditions, a considerable amount of long-distance-transported pollen can be deposited far from its place of origin. In extreme arid regions, in most cases, such situations occur and increase the difficulty to interpret fossil pollen records. In this study, three sets of Cour airborne pollen trap were installed on the northern slope of Tianshan Mountains to collect airborne Picea schre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Beer et al 2007;Huang et al 2015) and were likely derived from the lower arid steppe expanding in elevation between 1600-2000 m.a.s.l.Pinus-type pollen was found only in the ice below 75.8 m. As mentioned earlier, Picea is the dominant coniferous tree in the Tien Shan Mountains, but no Pinus tree is present in the modern forest in this region(Beer et al 2007;Pan et al 2013;Huang et al 2015).…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…Beer et al 2007;Huang et al 2015) and were likely derived from the lower arid steppe expanding in elevation between 1600-2000 m.a.s.l.Pinus-type pollen was found only in the ice below 75.8 m. As mentioned earlier, Picea is the dominant coniferous tree in the Tien Shan Mountains, but no Pinus tree is present in the modern forest in this region(Beer et al 2007;Pan et al 2013;Huang et al 2015).…”
mentioning
confidence: 52%
“…Abundance became low and peaks were smaller below 60 m. In the layers below 80 m, the abundance slightly increased, and some higher peaks (10-40 grains mL −1 ) appeared between 81.0 and 83.2 m depth. Picea pollen is most likely from Picea schrenkiana, which is the most dominant coniferous tree in the Tien Shan Mountains and is distributed on the slope of the northern side of the Grigoriev Ice Cap (Beer et al 2007;Pan et al 2013;Huang et al 2015).…”
Section: Pollen Profiles In the Ice Corementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is generally considered that Picea pollen has low dispersal ability, with most pollen grains falling within hundreds of meters from their parent trees (Jackson, 1990;Bittencourt and Sebbenn, 2007). Modern surveys have also confirmed that Picea pollen percentages can reach more than 30% in surface samples collected 30 m away from the Picea forests, while they decreases to 9e30% and 3e5% with the distance increasing to 15 km and 50e110 km, respectively (Li, 1991;Zhu et al, 2004;Pan et al, 2013. ).…”
Section: Vegetation and Climate During The Lgmmentioning
confidence: 90%